Apoptosis, senescence, and autophagy in rat nucleus pulposus cells: Implications for diabetic intervertebral disc degeneration12. Issue 5 (13th December 2012) - Jiang, Libo; Zhang, Xiaolei; Zheng, Xuhao; Ru, Ao; Ni, Xiao; Wu, Yaosen; Tian, Naifeng; Huang, Yixing; Xue, Enxing; Wang, Xiangyang; Xu, Huazi
Abstract This research was aimed to study the mechanisms by which diabetes aggravates intervertebral disc degeneration (IDD) and to discuss the relationship between autophagy and IDD in nucleus pulposus (NP) cells. Sixteen weeks after injecting streptozotocin (STZ), the intervertebral discs (IVDs) were studied by histology, Alcian blue, 1, 9‐dimethylmethylene blue (DMMB), immunohistochemistry, and RT‐PCR to explore the IDD. The apoptosis and senescence of NP cells was investigated by terminal deoxyribonucleotidyl transferase (TDT)‐mediated dUTP‐digoxigenin nick end labeling (TUNEL) assay, immunohistochemistry, and Western blot for caspase3, caspase8, caspase9, and p16lnk4A (increased in cellular senescence). The level of autophagy in NP cells was detected by Western blot, immunohistochemistry, and transmission electron microscopy (TEM). The proteoglycan and collagen II in the extracellular matrix and the aggrecan and collagen II mRNA expression in NP cells of diabetic rats were decreased compared with the control group. Diabetes increased apoptosis of NP cells and led to activations of initiators of intrinsic (caspases‐9) and extrinsic (caspase‐8) pathways as well as their common executioner (caspase‐3). Cellular senescence was increased about twofold in NP of diabetic rats. In addition, the Western blot, immunohistochemistry, and TEM demonstrated higher level of autophagy in NP cells of diabetic rats than control rats to a statistically significant extent. These findings support that diabetes induced by STZ can cause IDD by accelerating the apoptosis and senescence of NP cells excluding the overweight influence. And the results suggest that the autophagy may be a response mechanism to the change of NP cells in diabetic rats. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 692–702, 2013